Development of River Port (Kelotok) In Penajam Paser Utara and Balikpapan by using BOR, LF, AHP and Triangulation Analysis - Arief Hidayat; Johannes Diva Mahendra; Shintaro Terabe (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
The River Port in Penajam Paser Utara, East Kalimantan, serves as a vital transportation link connecting the coastal areas between Penajam Paser Utara and Balikpapan. Despite its strategic role, the port currently faces challenges, including limited berth capacity, insufficient supporting facilities, and low operational efficiency in River water transport services. This study, conducted in 2024, aims to analyze the operational characteristics of the River Port and transportation system, evaluate dock efficiency using the Berth Occupancy Ratio (BOR) and Load Factor (LF) methods, and determine infrastructure and service development priorities through the Analytic Hierarchy Process (AHP) approach. The research employs a quantitative, descriptive-analytical method that integrates primary and secondary data. The results show that the port’s operational performance requires improvement in dock utilization efficiency and passenger load distribution. Development priorities emphasize increasing transport capacity, optimizing service schedules, enhancing accessibility, and providing essential facilities such as comfortable waiting areas and improved safety systems. The findings highlight that sustainable River transportation development is crucial to supporting urban mobility and regional economic growth in East Kalimantan. Strategic recommendations from this study are expected to strengthen the competitiveness and reliability of River Port services.